Feasibility of Cord Blood Application in Cell Therapy for Central Nervous System Pathologies - Shcheniavskyi, Ivan; Salnikov, Dmytro; Chub, Oleg; Prokopiuk, Olga (Problems of Cryobiology and Cryomedicine, 2024)
This paper presents a search and analysis of scientific papers reporting about the findings aimed to elucidate the possibility of using cord blood (CВ) for therapy of nervous system pathologies. The authors found neither clinical protocols nor recommendations that have the valid or official status, etc. But a significant number of clinical trial protocols for treating neurological diseases with CB cell transplantation have been published. The review shows the results of some experimental studies in the models of central nervous system pathologies and clinical trials that have studied the CB therapeutic potential. The analysis of these reports suggests the prospects for using CВ in therapy of various pathologies, including neurodegenerative ones. However, further profound, targeted and well-funded research and extended clinical trials are needed to realize the therapeutic potential of CВ. The authors believe that in the nearest future it will be essential to study a paracrine effect of transplanted stem cells as an alternative to cell therapy. Probl Cryobiol Cryomed 2024; 34(3):165–185